Faktor – Faktor Yang Mempengaruhi Akuntanbilitas Pengelolaan Dana Desa Melalui Penerapan Sistem Keuangan Desa (Siskeudes) Pada Desa Di Kec. Waru Kab. Sidoarjo - Aaqilah Rihhadatul’ Aisy; Muhammad Taufiq Hidayat (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research is aimed to analyze influence of village governmental’s role, its competency, siskaudes application’s as moderating effect to village fund accountability. This research has 39 waru village government’s as sample and analyzed using PLS software. Data analysis has several step. First, reliable test is done. Then outer model and inner model are planed. All the instruments are valid and reliable. This research implied that govermantal role and its competency affect to fund accountability. Meanwhile, siskaudes application’s does not have any affect to fund accountability.